Transformational theology in a context of division : examining Belfast's separation barriers through a theological lens of idolatry - Hatch, Jonathan R. (Irish School of Ecumenics, 2013)
This dissertation addresses two central, interrelated questions. The first question is: How might a transformational theology be formulated that Is Informed equally by the legacy of Latin American liberation theology and theologies of reconciliation ?
Keywords: Religions, Theology & Ecumenics Ph.D.; Ph.D. Trinity College Dublin.